Compatibility Study of DNTF with Some Insensitive Energetic Materials and Inert Materials. Issue 4 (1st October 2016) - Li, Xi; Wang, Bo-Liang; Lin, Qiu-Han; Chen, Li-Ping
Abstract : The compatibility of 3, 4-dinitrofurazanfuroxan (DNTF) with insensitive energetic materials and inert materials was studied in detail using differential scanning calorimetry (DSC). 2, 4, 6-Trinitrotoluene (TNT), 2, 4, 6-triamino-1, 3, 5-trinitrobenzene (TATB), 3-nitro-1, 2, 4-triazol-5-one (NTO), 2, 6-diamino-3, 5-dinitropyrazine-1-oxide (LLM-105), 2, 6-diamino-3, 5-dinitropyridine-1-oxide (ANPyO), and 5-amino-1H-tetrazole nitrate (5-ATEZN) are used as insensitive energetic materials, and polymer(vinyl acetate) (PVAC), hydroxyl-terminated polybutadiene (HTPB), dinoctylsebacate (DOS), 2, 4-dinitrotoluene (DNT), and wax are used as inert materials. The results show that DNTF/TNT and DNTF/5-ATEZN possess good compatibility, DNTF/NTO and DNTF/TATB have moderate compatibility, and the compatibility of DNTF/LLM-105 and DNTF/PVAC is poor; in addition, DNTF/ANPyO, DNTF/HTPB, DNTF/DNT, DNTF/DOS, and DNTF/wax have bad compatibility.